Impact of Modernization on Socio-economic Development of Manipuri Communities: A Sociological Studies - Mitu Chowdhury (Journal of Sociological Research, 2024)
The Manipuri communities are very industrious. Very rich or extremely poor families are rare among them. So they do not work as day labourer or rickshaw puller. This is the expression of their modernism. This study was conducted an informative research work on the effects of modernization on the socio-economic development of Manipuri people. Five sampling areas were selected purposively – Kewa para, Sibganj, Noya bazar, Lama bazar and Sagar dighir par Manipuri para of Sylhet city in Bangladesh. Following a systematic sampling, a total number of 100 Manipuris participants were selected from the 20 families from each of the 5 sampling. This study also revealed that most of the respondents 73% have educational qualification between SSC to Master Degree. Above 28% respondents are slight modern and 24% respondents are modern. So it proved that impact of modernization on profession. The observed that the Manipuri people are suffering from various diseases like diarrhoea, dysentery, gastric, coughing, rheumatic fever. Around highest 60% respondents are took allopathic treatment. It was a positive response to modernization. The finding of the current research might be helpful to future national policies of Bangladesh.